2022
DOI: 10.3389/fchem.2022.837032
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-Coated Mesoporous Silica Nanoparticle for Magnetic Resonance Imaging

Abstract: Magnetic resonance molecular imaging can provide anatomic, functional and molecular information. However, because of the intrinsically low sensitivity of magnetic resonance imaging (MRI), high-performance MRI contrast agents are required to generate powerful image information for image diagnosis. Herein, we describe a novel T1 contrast agent with magnetic-imaging properties facilitated by the gadolinium oxide (Gd2O3) doping of mesoporous silica nanoparticles (MSN). The size, morphology, composition, MRI relaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…12,13 Also doping the gadolinium oxide particles with mesoporous silica enhanced T1 contrast of gadolinium due to silica geometrical connement. [14][15][16] Recent studies have revealed that the conjugation of Gd 3+ complexes with iron oxide NPs, and the combination of Gd 2 O 3 NPs with other magnetic materials, such as Fe 3 O 4 NPs into single composite particles leads to the enhancement of T1 and T2 contrast in MRI. In case of a thin gadolinium shell, nanocomposites provided higher relativity than a thick shell during MRI examinations.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Also doping the gadolinium oxide particles with mesoporous silica enhanced T1 contrast of gadolinium due to silica geometrical connement. [14][15][16] Recent studies have revealed that the conjugation of Gd 3+ complexes with iron oxide NPs, and the combination of Gd 2 O 3 NPs with other magnetic materials, such as Fe 3 O 4 NPs into single composite particles leads to the enhancement of T1 and T2 contrast in MRI. In case of a thin gadolinium shell, nanocomposites provided higher relativity than a thick shell during MRI examinations.…”
Section: Introductionmentioning
confidence: 99%
“…The MSNs (Gd 2 O 3 @MSN) were prepared in accordance with our previous research [ 57 ]. In brief, a mixture of NaOH (140 mg) and CTAB (500 mg) in ddH 2 O (220 mL) was stirred at 80 ℃ for 1 h. Subsequently, the TEOS (1.5 mL) was added dropwise to the above mixture through appropriate stirring (250 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…Eriksson et al [61] used a survey to improve T 1 -weighted image contrast at the lower dose of Gd ions in cerium oxide NPs as a T 1 -weighted MRI contrast agent and achieved positive results. It has been demonstrated that a high T 1 relaxivity of Gd oxide (Gd 2 O 3 ) conjugated with mesoporous silica NPs (Gd 2 O 3 @MSNPs) in comparison with Gd diethylene triamine pentaacetate (Gd-DTPA) results in in-vivo use of Gd 2 O 3 @MSNPs as a T 1 -weighted MR image contrast agent [62]. In an investigation into the clinical use of ultrasmall GdNPs (Gd@PEG NPs), Wang et al [63] found that monodispersible ultrasmall GdNPs can be used for diagnosis of kidney dysfunction through the in-vivo T 1 -weighted MR imaging.…”
Section: Gadolinium-based Nanoparticlesmentioning
confidence: 99%